Effects of Testosterone Therapy on Cognitive Function in Aging: A Systematic Review. Issue 3 (September 2016) - Hua, Jeremy T.; Hildreth, Kerry L.; Pelak, Victoria S.
Abstract : Endogenous testosterone in the aging man has been scrutinized extensively in regard to its effects on performance in many cognitive domains, especially verbal fluency, visuospatial and visuoperceptual abilities, memory, and executive function. Studies of testosterone supplementation have sought to identify potential cognitive improvements in men with and without baseline cognitive impairment, and have had a wide range of results. The variability in outcomes is likely related, in part, to the lack of consensus on methods for testosterone measurement and supplementation and, in part, to the disparate measures of cognitive function used in randomized controlled studies. Despite the limitations imposed by such inconsistent methods, promising associations have been found between cognition and testosterone supplementation in both eugonadal men and men with low testosterone levels, with and without baseline cognitive dysfunction. This systematic review highlights the cognitive measures used in and the outcomes of existing studies of testosterone and cognition in aging men. The review suggests that larger studies and a more standardized approach to assessment will be needed before we can fully understand and realize sustained benefits from testosterone supplementation in the elderly male population, particularly given the substantial increase in testosterone supplementation in clinical practice.